The role of organizational culture in achieving job satisfaction among employees in higher education institutions: (Salahuddin University as a model) - Shangar Jamal Naqshbandi's (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The goal of the research is to shed light on the role of organizational culture in achieving job satisfaction among workers in higher education institutions (Saladin University as an example). Through reviewing the literature in the field of organizational culture and job satisfaction, it was found that researchers in the field of management emphasized the importance of organizational culture orientation. In achieving job satisfaction in organizations, therefore, it is necessary for organizations, whether private or governmental, to focus on human resources because they are a basic pillar of orientation, and given that organizational culture has an important role on the behavior and actions of workers within the organization. If there were 70 respondents and 62 of them were valid for analysis, the measurement tool was used to analyze the questionnaire through the statistical software SPSS using a Likert scale that included the two hypotheses: the independent variable (organizational culture) and the dependent variable (job satisfaction). The researcher reached conclusions and recommendations and but the most important of them is the presence of a positive effect of the dimensions of organizational culture in achieving job satisfaction, with the existence of a strong positive and moral relationship between the dimensions of organizational culture and achieving job satisfaction. Job satisfaction is a guarantee of employees’ continuity of production, creativity and excellence.